2022
DOI: 10.1177/2333794x211065335
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Examination of Perceived Stigma and its Sources Among Adolescents Living With HIV in Western Kenya

Abstract: Introduction. Adolescents (10-19 years) living with HIV (ALWH) face unique challenges in controlling HIV long-term, including stigma and perception of stigma within their communities. Methods. We conducted a qualitative investigation of the sources of perceived HIV-related stigma with ALWH in western Kenya. Forty-six ALWH on ART, aware of their status, and engaged in care were enrolled. Interviews explored perceived stigma by probing the individuals and experiences that adolescents identify as causing or perpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…The relationship between perceived stigma, and status non-disclosure has been reported elsewhere ( 77 ). Moreover, this finding supports other studies that have found a link between mental health and perceived HIV stigma ( 33 , 78 ). Additionally, most participants expressed their mental health challenges using idioms like “thinking too much,” “dislike you,” “become sad,” and “hate you,” which can be equated to the local understanding of mental health challenges.…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between perceived stigma, and status non-disclosure has been reported elsewhere ( 77 ). Moreover, this finding supports other studies that have found a link between mental health and perceived HIV stigma ( 33 , 78 ). Additionally, most participants expressed their mental health challenges using idioms like “thinking too much,” “dislike you,” “become sad,” and “hate you,” which can be equated to the local understanding of mental health challenges.…”
Section: Discussionsupporting
confidence: 91%
“…These concerns are shared by YLWH in other work in Kenya, who have expressed fear of sharing their HIV status, whether purposefully or accidentally, due to experienced, anticipated, and internalized stigma. 8,9,27,3133 It is well-documented that HIV-related stigma impacts care-seeking and other behaviors among YLWH, and this study's findings demonstrate that fear of stigma also affects how YLWH engages in research. 27,34 Globally, studies have shown that HIV disclosure can be associated with feelings of isolation, anxiety, depression, negative self-image, and internalized blame.…”
Section: Discussionmentioning
confidence: 61%
“…8,9,27,3133 It is well-documented that HIV-related stigma impacts care-seeking and other behaviors among YLWH, and this study's findings demonstrate that fear of stigma also affects how YLWH engages in research. 27,34 Globally, studies have shown that HIV disclosure can be associated with feelings of isolation, anxiety, depression, negative self-image, and internalized blame. 3539 It is, therefore, critical to ensure that adequate protections are in place to protect the confidentiality of research participants’ HIV status and minimize the risk of accidental disclosure and associated negative outcomes.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations